How safety leadership influences employee safety participation and compliance through safety knowledge: the moderating role of psychological resilience - Piao, Juanxiu; Hahn, Juhee (Frontiers in Psychology, 2025)
IntroductionThis study developed a multilevel model to examine the mechanisms that link safety leadership to employee safety behaviors. We investigated (a) the mediating role of individual safety knowledge in the correlation between team-level safety leadership and employees’ safety compliance and participation, and (b) the moderating role of psychological resilience in this mediation process.MethodsWe gathered three-wave survey data from 505 frontline employees and 88 supervisors within China’s electric power industry.ResultsHierarchical Linear Modeling (HLM) analysis confirmed that safety leadership positively influenced both safety compliance and participation. Employee safety knowledge significantly mediated this relationship. Furthermore, psychological resilience moderated this process: the positive effect of safety knowledge on both safety compliance and participation is stronger among employees with high psychological resilience.DiscussionThese findings indicate that organizations should invest in safety leadership training to enhance employee knowledge and foster psychological resilience as a crucial personal resource, enabling employees to more effectively convert safety knowledge into safe behavior.